A VIOLÊNCIA DOMICILIAR CONTRA CRIANÇAS E ADOLESCENTES E A RESPONSABILIDADE DOS PROFISSIONAIS DE SAÚDE: UMA REVISÃO BIBLIOGRÁFICA - Liliane Souza Pereira; Rebecca Silva e Costa; Laís Ferreira Carrijo; Guilherme Quireza Silva; Marilúcia Batista Silva (UniEVANGÉLICA, 2015)
Objective: The study aimed to discuss the violence against children and adolescents and the responsibility of health professionals in the identification and notification of these events. Data source: A bibliographic survey was carried out on the portal of the Virtual Health Library, in order to identify the publications on the theme of violence against children and adolescents, including terms related to notification of cases of ill-treatment. The research was carried out from August to November 2012 and was selected publications in the period of 2001 to 2012, in addition to institutional material from the Ministry of Health and relevant legislation about the issue researched. Data synthesis: The study demonstrated that the National Policy for the Reduction of Morbidity and Mortality from Accidents and Violence has become a compulsory notification of all cases, suspected or confirmed abuse, in order to trigger a process that aims to stop attitudes and violent behavior on the part of any aggressor, in addition to promoting care socio-health focused on the protection of the victims. However, unprepared to deal with such situations, many professionals will no longer perform the notification by believing that the violence is a fact that belongs to legal and public safety, not characterizing a health problem. Conclusions: It is concluded that there is a gap in the notifications and identifications of these cases by health professionals and, therefore, the implementation of programs of continuing education services is essential.